AN EXPERIMENTAL STUDY OF THE LOW-TEMPERATURE SULFURIZATION OF CARBOHYDRATES - van Dongen B.E.; Schouten S.; Baas M.; Geenevasen J.A.J.; Sinninghe Damste J.S. (My University, 2003)
Sulfurization of carbohydrates has been suggested as an important mechanism for the preservation of organic matter. To study this process, different monosaccharides were sulfurized under laboratory conditions at relatively low temperature (50 °C). The products formed after cleavage of polysulfide linkages were analyzed using gas chromatography (GC) and gas chromatography/mass spectrometry after appropriate derivatization. Selected products were isolated by preparative GC and their structures were identified by nuclear magnetic resonance spectroscopy. During these experiments all monosaccharides were completely converted into organic sulfur compounds (OSCs) and monosaccharides with the carbonyl function replaced by sulfur formed a substantial part of the GC-amenable OSCs. The structures of other OSCs formed indicated that cleavage of C-C bonds and racemization also took place during these experiments. The yield of recoverable OSCs after cleavage of polysulfide linkages was relatively low (<5% of the starting monosaccharide), indicating that most of the sulfurization products were still non GC-amenable and thus, for example, linked through monosulfide linkages. Flash pyrolysates of the sulfurized carbohydrate material contained in all cases relatively high amounts of short-chain alkylated (C0-C5) thiophenes, comparable to those obtained from S-rich kerogen. The structure of the monosaccharide used in the experiments had no effect on the alkylthiophene distribution. These results provide experimental evidence that sulfurization of monosaccharides at relatively low temperatures can result in the formation of OSCs, most likely starting with sulfurization of the carbonyl functionality. Preservation of carbohydrates through sulfurization may thus be an important pathway of preservation of organic matter in anoxic depositional environments.